Hubungan Kualitas Interaksi (Interaction Quality) Dengan Kepuasan Pasien Umum Di Ruang Rawat Interna Dan Anak RS Syekh Yusuf Kabupaten Gowa - Andi Ridwan Jalal; Andi Asrina; Haeruddin Haeruddin (An Idea Health Journal, 2024)
Hospitals as health facilities play a vital role in providing efficient and quality services. The quality of health services that are in line with the code of ethics and professional service standards is expected to create satisfaction for patients. This research is an analytical observational study using a cross sectional study approach. The research population was general patients undergoing treatment in internal and pediatric wards for 1 month. The sampling method used accidental sampling, with a total sample of 37 people. Data analysis was carried out using the chi-square statistical test. The quality of interaction has a significant relationship with patient satisfaction (p-value 0.001 < 0.05). The patient satisfaction variable at Syekh Yusuf Hospital, Gowa Regency is significantly related to the quality of interaction. These findings provide important insights for efforts to increase patient satisfaction at these hospitals. This research can be the basis for developing health care interaction strategies to increase patient satisfaction. The results of the research can be a basis for hospitals in identifying and improving certain aspects of health services in order to increase the level of patient satisfaction in providing optimal health services at Syekh Yusuf Hospital, Gowa Regency.